Are ice hockey players becoming faster and stronger? A nine-year trend study of the Swiss U18 men`s ice hockey national team - Bielmann, C.; Andrey, P.; Fischer, K.; Strübi, J.; Maystre, H.; Castella, L.; Hess, N.; Tschopp, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Physical performance, including speed, power, strength, and endurance are considered critical success factors in elite ice hockey. Several studies have shown overall improvements in these qualities among elite-male ice hockey players over the years 1979-2005 (e.g. Quinney et al., 2008). The last decade has received less attention to date. Anecdotal evidence suggests that today`s players are faster, stronger, and more agile than players were 10 years ago. However, there are no data confirming this claim so far. The aim of this study was therefore to examine physical and physiological changes among the Swiss U-18 men`s ice hockey national team over the years 2011-2019.